The Impact of Chamotte Sand on the Mechanical and Physical Characteristics of Ceramic Molds Made of Chromite Sand - Ellyawan Setyo Arbintarso; Sugeng Slamet; Rahayu Khasanah; Suharto Suharto; Riswan Aliyadi; Andri Trihendriana (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
Casting flaws are common in the high-temperature steel casting process, particularly surface flaws and rough surfaces. One option to avoid these surface defects is to use sand with a higher melting point, like chromite sand. This study is an extension of the previous research, which found that chromite sand, a ceramic mold material, frequently fractures during the sintering process. Chamotte sand material of 3% and 5% by weight has been applied as a binder to chromite sand to improve this. With an ideal sintering temperature of 1,050°C, two ceramic sintering processes, the Shaw and the Unicast processes—have been used. To determine the chromite-chamotte sand mixture's potential as a ceramic mold material, tests for cold crushing strength (CCS), modulus of rupture (MoR), permeability, and refractory were conducted. The mixture with 3% wt chamotte sand with the Shaw sintering technique provided the highest results and was appropriate for ceramic mold.